2014
DOI: 10.1177/1471082x13494532
|View full text |Cite
|
Sign up to set email alerts
|

Birnbaum–Saunders statistical modelling: a new approach

Abstract: Modelling based on the Birnbaum-Saunders distribution has received considerable attention in recent years. In this article, we introduce a new approach for Birnbaum-Saunders regression models, which allows us to analyze data in their original scale and to model non-constant variance. In addition, we propose four types of residuals for these models and conduct a simulation study to establish which of them has a better performance. Moreover, we develop methods of local influence by calculating the normal curvatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 39 publications
0
49
0
10
Order By: Relevance
“…All statistical modeling must be evaluated by diagnostic tools. One of the most used tools in regression models is the residual analysis, which is a very useful technique to detect departures from the model assumptions and to identify atypical observations . We consider in this paper two types of residuals for log‐symmetric regression models.…”
Section: Log‐symmetric Regression Models and Information Criteriamentioning
confidence: 99%
“…All statistical modeling must be evaluated by diagnostic tools. One of the most used tools in regression models is the residual analysis, which is a very useful technique to detect departures from the model assumptions and to identify atypical observations . We consider in this paper two types of residuals for log‐symmetric regression models.…”
Section: Log‐symmetric Regression Models and Information Criteriamentioning
confidence: 99%
“…We use the notation U ∼BS( μ , δ ) and its PDF is given by fUfalse(u;μ,δfalse)=expfalse(δfalse/2false)δ+140.1emu320.1emπμ()u+δμδ+1exp()δ4()ufalse(δ+1false)δμ+δμufalse(δ+1false),1emu>0. Some appealing properties of the BS distribution are the following. If U ∼BS( μ , δ ), then (i) c U ∼BS( c μ , δ ), with c > 0, which means that the BS distribution is closed under scalar multiplication (proportionality); (ii) 1/ U ∼BS( μ ⋆ , δ ), where μ ⋆ = ( δ + 1)/( δ μ ), implying that the BS distribution is closed under reciprocation; (iii) the median of the distribution of U is ( δ /( δ + 1)) μ , which can be directly obtained when q = 0.5 from its quantile function given by u(q;μ,δ)=FU1(q;μ,δ)=δμ/(δ+1)z(q)/2δ+z(q)/2δ2+12,0<q<1, where z ( q ) is the q × 100th percentile (or quantile function) of the standard normal distribution and FU1 is the inverse of the cumulative distribution function (CDF) F U ; (iv) the BS distribution has different shapes for its PDF, which cover high, medium, and low asymmetry; (v) the new parameterization of the BS distribution based on the mean permits us to analyze data in their original scale, avoiding problems of interpretation in models based on logged data; (vi) in frailty models, the BS distribution is highly competitive in terms of fitting…”
Section: Preliminariesmentioning
confidence: 99%
“…Consider a reparameterized version of the BS (RBS) distribution by setting κ = 2/τ and σ = τ µ/[τ + 1], such that τ = 2/κ 2 and µ = σ[1 + κ 2 /2], where τ > 0 is a shape and precision parameter and µ > 0 is a scale parameter and the mean of the distribution; see Leiva et al (2014a) and SantosNeto et al (2016). In this case, the PDF of X ∼ RBS(µ, τ ) is given by…”
Section: A Reparameterized Bs Distributionmentioning
confidence: 99%
“…Bhatti (2010) suggested that (B2) might possibly: (C1) improve the model fit, since for asymmetric, heavy-tailed distributions, as occurs with TD data, the median is often considered as a better measure of central tendency than the mean; and (C2) increase the forecasting ability due to the fact that the mean is greater than the median for skew distributions. In this context, we consider two models: A first new mean-based model (BSACD1 in short) specified in terms of a time-varying conditional mean duration, as usual in ACD models, using a reparameterized version of the BS distribution (see Leiva et al, 2014a;Santos-Neto et al, 2016); and a second median-based model (BSACD2 in short) specified in terms of a time-varying conditional median duration. Thus, the primary objective of this paper is to compare both BSACD1 and BSACD2 models.…”
Section: Introductionmentioning
confidence: 99%